Accrual Accounting and the Australian Public Sector – A Legitimation Explanation - Nicholas Davis (Australasian Accounting, Business and Finance Journal, 2010)
The move from the cash basis to the accrual basis of accounting in the Australian Public Sector (APS) was a key element of the New Public Management (NPM) reform program and an event of historical significance. The aim of this paper is to identify key events in this transition and to analyse them through the theoretical lens of Habermas' (1976) theory of legitimation. Key elements of the literature concerning accrual accounting in the APS are reviewed, together with a discussion of the relevance of Habermas (1976) to this study. These critical historical events are then analysed according to Habermas (1976). The central argument expressed within this paper is that accrual accounting can be seen to be a device used by different levels of government in the APS in an attempt to combat the tendencies for economic, rationality and legitimacy difficulties that are commensurate with welfare state societies such as Australia.
Keywords: Accrual accounting; Public sector; Habermas; Legitimation; Literature; Accounting history